2012
DOI: 10.1029/2012gl052511
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of the Mount Steller landslide flow history and of the generated long period seismic waves

Abstract: The rock‐ice avalanche that occurred in 2005 on Mount Steller, Alaska and the resulting long period seismic waves have been simulated for different avalanche scenarios (i.e., flow histories), with and without erosion processes taken into account. This 40–60 Mm3avalanche traveled about 10 km down the slope, mainly on top of a glacier, eroding a significant amount of ice. It was recorded by 7 broadband seismic stations. The simulations were compared with the recorded long period seismic signal and with the inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
154
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(165 citation statements)
references
References 25 publications
(41 reference statements)
7
154
0
Order By: Relevance
“…Although the driving forces are overestimated in thin layer depth-averaged models, leading to overestimates of the initial velocity by up to 20% for aspect ratios aC1 the deposits are correctly reproduced. Recent simulation of the seismic waves generated by the flow along the topography and comparison with seismic records suggest that the landslide dynamics are also well reproduced by these numerical models 28,29,50 .…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…Although the driving forces are overestimated in thin layer depth-averaged models, leading to overestimates of the initial velocity by up to 20% for aspect ratios aC1 the deposits are correctly reproduced. Recent simulation of the seismic waves generated by the flow along the topography and comparison with seismic records suggest that the landslide dynamics are also well reproduced by these numerical models 28,29,50 .…”
Section: Methodsmentioning
confidence: 97%
“…Experimental work 4 has shown that the mean velocity is B2.5 times greater on a slope of 22°than that on a flat bottom. Although new constraints on landslide velocities on Earth are emerging from seismological observations 28,29 and from a few rock avalanches that have been observed and/or filmed in situ 25 , the simulation approach adopted here is the only way to quantitatively recover landslide velocities for remote and past events on Earth and beyond.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This induces significant differences in the profile of the spreading mass and of the deposit with runout distances more than 10% larger and velocities that could be more than 20% heigher in the simple test of granular collapse over inclined plane performed here. While it is quite difficult to measure experimentally or in the field the fluid and solid velocities, the use of seismic waves generated by debris flows or avalanches may be a new way to discriminate between these two models ( [9], [31]). An advantage of our model is that the closure equation (i. e. incompressibility of the solid phase) is explicitly imposed, making it possible to derive physical interpretation of our results while in the PL model, the behavior is dictated by the imposed zero-pressure at the surface of each phase, without any description of the mechanical properties of the solid phase.…”
Section: Resultsmentioning
confidence: 99%